El paisaje monumental conmemorativo de la batalla de San Carlos en la diacronía: latencias y tensiones (Buenos Aires, Argentina, 1872) - Carlos Landa; Graciela Waks; Jimena Doval; Jerónimo Angueyra (Antípoda: Revista de Antropología y Arqueología)
This article explores the commemorative monumentality of the Battle of San Carlos, focusing on material evidence, documentary sources, and oral memory spanning nearly a century of monumental landscape (1935-2024) at the site of Los Cuatro Vientos (Bolívar, Buenos Aires, Argentina). By examining these landscapes as activators of memory, this study sheds light on their role in shaping and perpetuating hegemonic discourses that overlap, persist, and conflict over time, as well as the social actors involved. The objective is to understand the monument’s place within dominant narratives and the sociohistorical context of each period as part of its social history. Archaeology, as a science of traces, reveals not only the phases or stages of monumentality but also attempts at erasure, damage, or decay due to time and environmental factors, uncovering multiple layers of meaning that can be excavated both literally and metaphorically. Far from being a static landscape, the site is continually redefined through new meanings, social actors, commemorative practices, and performative actions. In contemporary times, conflicting discourses and materialities coexist within the landscape. Like all representations of the past, the monument selectively relates to historical events, contributing to both remembrance and oblivion, including and excluding, exalting and concealing, amplifying certain voices while silencing others. Initially, this monument was intended to symbolize the triumph of civilization over the so-called barbarism of the desert, casting the indigenous population as the defeated, relegated to invisibility through their forced incorporation into the Argentine nation-state. However, the memory of the defeated persists, latent within the city and embedded in the landscape’s folds.